Fuzzy logic based plantwide control applied to ethanol production from potato starch - Amanda Fonseca Oliveira; Félix Rezende Santos; Rodolpho Rodrigues Fonseca (The Journal of Engineering and Exact Sciences)
Industrial plants dedicated to ethanol production have a large number of interrelated processes and operations with nonlinear dynamics, requiring a process control design method considering plantwide aspects and nonlinear control techniques application, as fuzzy logic, to overcome disturbance effects on process control performance. In this work, disturbance in an ethanol process plant were investigated in order to propose a fuzzy system to improve the plantwide control and keep process productivity. The fuzzy system was set to adapt the bioreactor temperature setpoint in case of disturbances, avoiding process deregulation. The results indicated that the fuzzy system developed was able to improve plantwide process control performance and also increasing process productivity.